Chemical composition and antimicrobial activity of three Pimenta racemosa var. ozua (Myrtaceae) extracts from the Dominican Republic - Tania Muñoz-Martinez; Lolymar de los Ángeles Romero; Luis Orlando Maroto-Martín; Yameiri Mena (Acta Scientiarum. Biological Sciences, 2025)
Ozua is an endemic flowering plant from the island of Hispaniola belonging to the Myrtaceae family. Many Caribbean species within this family remain phytochemically unexplored, including Pimenta racemosa var. ozua Urb. & Ekman. While some studies have investigated the anti-inflammatory, antinociceptive, and anti-ulcerogenic properties of ozua, the antimicrobial potential remains unknown. In this investigation, the essential oil (EO), ethanolic extract (EE), and petroleum ether extract (PEE) of Pimenta racemosa var. ozua were analyzed to determine their chemical composition and antimicrobial activity against ten microorganisms of clinical interest. The extracts were obtained via steam distillation and Soxhlet extraction. The main secondary metabolites were quantified by spectrophotometric assays, and phytochemical profiles were established by gas chromatography-mass spectrometry (GC-MS). In vitro antimicrobial assays were performed using agar-well diffusion, and multi-well dilution assays to determine the minimum inhibitory concentrations (MICs). The profiles obtained showed an abundance of terpenoids, and terpenes in the EO, while tocopherols and phytosteroids predominated in the Soxhlet extracts. EO exhibited significant antibacterial activity, EE showed antimicrobial activity, and PEE demonstrated limited activity against Pseudomonas aeruginosa.